(untitled) (Nexo Revista Científica, 2021)
When constructing buildings and engineering structures it is necessary to make a pit for the foundation construction. Excavation works, construction of buildings and engineering structures change the deformation-strength properties of soils, which lie under the foundations. To study the changes in engineering-geological conditions during 2016-2018, on one of the construction sites in Chita (Russia), a well was made to take a soil sample and laboratory studies on physical and mechanical properties of soils were performed. As a result of the studies, it was established that the deterioration of the soils’ deformation characteristics under the foundations increased by 2.5 times, from 20 MPa to 8 MPa. The strength characteristics changed almost by 2 times. The soil’s specific cohesion changed from 31 MPa to 16 MPa due to freezing and thawing of the soil on the excavation face of the pit with its subsequent soaking. It is necessary to carry out additional activities to strengthen and stabilize the foundations.